Pembuatan Mesin Internal Mikser Bijih Plastik Kapasitas 50 g/h - Purba, Jepriadi; Iswandi, Iswandi; Umroh, Bobby (Jurnal Ilmiah Teknik Mesin & Industri (JITMI), 2023)
This research aims to test and validate the performance of the IMBP Machine that has been created, ensuring that the machine can operate effectively and perform its components' functions as expected. Additionally, the objectives of this study include achieving the desired processing results of 50 grams per hour of plastic seeds and systematically developing the process of manufacturing the IMBP Machine, starting from the construction of the iron frame, gear housing, end plate, barrel, hopper, cover, packing, knife shaft, blades, binding shaft, and finishing process. The research methodology employed encompasses field observation, literature review, testing and measurement methods, as well as analytical methods. Field observation is utilized to observe and gather data from machines operating in the field. Literature review is conducted to obtain information related to the theory and practices of the IMBP Machine. Testing and measurement methods are employed to evaluate machine performance and collect data regarding the achieved processing outcomes. Furthermore, the analytical method is used to compare the obtained data with the desired specifications, thus validating whether the machine has achieved the intended targets. The research findings demonstrate that this machine successfully produces the IMBP Machine according to the desired specifications. It is proven to function effectively in processing plastic and carbon materials. With the results of this research, it is expected that this machine can contribute positively to plastic waste processing and carbon waste reduction processes.